BEYOND ANTHROPOCENTRISM: RETHINKING HUMAN-ANIMAL RELATIONS IN COETZEE’S ELIZABETH COSTELLO AND MARTEL’S LIFE OF PI - Patowary, Upakul; Das, Kapahi; Talukdar, Dr. Jeuti (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The anthropocentric worldview, which places humans at the center of existence, has long shaped Western philosophy, literature, and ethics. However, in the wake of posthumanist and ecocritical movements, the boundaries between the human and non-human have been increasingly questioned. This paper explores the ethical and philosophical reconfiguration of human-animal relationships in Coetzee (2003) and Martel (2001). Both novels serve as literary meditations on the limits of empathy, reason, and the moral imagination that define humanity’s engagement with other living beings. Coetzee’s protagonist, Elizabeth Costello, becomes a vehicle through which the author interrogates Cartesian rationalism and argues for a “sympathetic imagination” that dissolves the rigid separation between human and animal consciousness. Similarly, Martel’s Life of Pi subverts traditional anthropocentrism through its allegorical narrative that questions the ethics of survival, coexistence, and the blurred distinction between man and beast. By reading both texts through the lens of posthumanism and critical animal studies, this paper argues that literature serves as an ethical laboratory for rethinking interspecies boundaries. The study highlights how both authors employ narrative strategies that decenter the human subject and envision a more inclusive form of being — one grounded in empathy, coexistence, and ecological awareness.